PEMBERDAYAAN PEDAGANG KAKI LIMA DI WILAYAH KOTA PALANGKA RAYA - Rohaetin Rohaetin (Jurnal Mediasosian : Jurnal Ilmu Sosial dan Administrasi Negara, 2019)
AbstractA developing city continues to be in tune with growth, population and management, so it also needs to be supported by regulatory growth. The physical growth of the city is in accordance with the plan, but the variations are sometimes escaped from the supervision of the stakeholders. However, all of that can be overcome with various existing regulations. The various variations in the growth of the city, one of the reasons for the migrant problem which has side effects, is the trade aspect, as is done by street vendors. The government faces a dilemma, they want to be prohibited from being legally citizens of the city, and this is to earn a living to survive, on the other hand they must be organized and empowered. A qualitative approach is used to dissect this problem and the researcher is the main instrument. The technique of determining informants is using purposive technique. Observation, interview and documentation are data collection techniques used. After the data has been collected, it is validated by comparing various data and analyzed using interactive analysis techniques. The result of this research is that they trade at night until midnight. In the fasting month they trade until dawn. They are provided with electric lights and are charged a levy every night. Selling outside the designated location is raided by the Civil Service Police Unit. The government arranges and empowers street vendors through various regulations.Keywords: Street Vendors; Arrangement; EmpowermentAbstrakKota terus berkembang seirama dengan pertumbuhan pembangunan, penduduk serta pengelolaannya, sehingga perlu didukung pula dari pertumbuhan regulasi. Pertumbuhan kota secara fisik sesuai dengan rencana, tetapi variasinya terkadang lepas dari pengawasan pemangku kebijakan. Namun demikian semua itu bisa diatasi dengan berbagai regulasi yang ada. Berbagai variasi dari pertumbuhan kota tersebut salah satu sebab masalah migran yang membawa dampak sampingan adalah aspek perdagangan, sebagaimana yang dilakukan oleh pedagang kaki lima. Pemerintah menghadapi dilema, mau dilarang mereka legal sebagai penduduk kota, dan hal tersebut sebagai mencari nafkah untuk bertahan hidup, disisi lain mereka harus ditata dan diberdayakan. Pendekatan kualitatif digunakan untuk membedah permasalahan ini dan peneliti sebagai instrumen utama. Teknik penentuan informan dengan teknik purposive. Observasi, wawancara dan dokumentasi merupakan teknik pengumpulan data yang digunakan. Setelah data terkumpul kemudian divalidasi dengan membandingkan berbagai data dan dianalisis dengan teknik analisis interaktif. Hasil penelitian adalah mereka berdagang pada malam hari sampai tengah malam. Pada bulan puasa mereka berdagang sampai waktu sahur. Mereka difasilitasi lampu listrik dan ditarik pajak retribusi setiap malamnya. Berjualan di luar lokasi yang telah ditentukan dirazia oleh Satuan Polisi Pamong Praja. Pemerintah melakukan penataan dan pemberdayaan pedagang kaki lima melalui berbagai regulasi.Kata Kunci: Pedagang Kaki Lima; Penataan; Pemberdayaan